Malignant Sertoli cell tumour in a cryptorchid canine with benign cystic prostatic hyperplasia: a case report - Laverde, Néstor (2023)
The case of an 8-year-old Beagle canine, who was attended at the ASMEVET veterinary hospital in the city of Tunja, Colombia, is presented. The owner reported that in recent months he has been losing hair, has increased water consumption, has not been neutered, and more recently is depressed, lack of appetite and with signs of dysuria. On physical examination, generalized alopecia and gynecomastia were observed, and the prostate was enlarged and asymmetric. Transabdominal ultrasonography revealed an enlarged prostate, with heteroechogenic parenchyma and microcysts, and the testicles were retained at the level of the apex of the bladder. Enrofloxacin was administered for 5 days, and meloxicam for 4 days, and then the patient underwent celiotomy to remove the retained testicles. The histopathological study reported malignant sertolinoma. Fine needle aspiration of prostate tissue revealed cells consistent with benign prostatic hyperplasia. After 90 days of bilateral orchiectomy, remission of alopecia was observed and ultrasound evaluation showed a decrease in the size of the prostate.